Evaluation of the Effectiveness of the Electronic Registration System in Resolving Property Disputes: Survey Research at the National Land Agency - Judijanto, Loso; Gunawan, M. Indra; Salopari, Nuryati; Sari, Ikka Puspita; Huspika, Syafrita; Marpi, Yapiter (Rechtsnormen: Journal of Law, 2024)
Background Electronic registration systems have become a significant innovation in modern property administration. In the context of the National Land Agency, the implementation of an electronic registration system aims to increase efficiency and transparency in resolving property disputes. However, the effectiveness of this system still needs to be thoroughly evaluated to ensure that these goals are achieved optimally.   The aim of the research is to evaluate the effectiveness of the electronic registration system implemented in resolving property disputes at the National Land Agency. By assessing the success of this system in facilitating the property dispute resolution process, the aim of this research is to provide in-depth insight into the extent to which this system can increase efficiency and transparency in the process.   The research method used is a survey involving relevant stakeholders in the property dispute resolution process at the National Land Agency. The survey will cover use of the electronic registration system, perceptions of the system's effectiveness, and feedback and suggestions for further improvement.   Research Results From the survey results, it can be concluded that the electronic registration system has made a positive contribution in increasing efficiency and transparency in resolving property disputes at the National Land Agency. The majority of respondents stated that this system speeds up the process, reduces administrative errors, and increases the accessibility of property-related information.   This research concludes that the electronic registration system is effective in resolving property disputes at the National Land Agency. However, there are several areas that still require improvements and updates to improve overall system performance. Thus, recommendations are given to continuously update the system in accordance with technological developments and user needs to ensure its effectiveness in the long term.